Natural Compounds as Potential Anti-COVID Agents - Rani, Nidhi; Singh, Randhir; Kumar, Praveen; Sharma, Prerna; Sharma, Vikas (Anti-Infective Agents, 2023)
Background: Since December 2019, COVID-19 has become a new health crisis in the world and has been declared a public health emergency of international concern by WHO. In search of anti-COVID treatment regimen, we applied molecular docking approach in order to identify the natural compounds that may have potential for anti-COVID treatment with specific target and selective inhibitory mechanism. Our goal is to identify the potential anti-COVID compounds based on virtual screening of the protein of spike glycoprotein as virtual inhibition target. Methods: Molecular docking was carried out by using Molergo Virtual Docker. 35 compounds from different plant sources were selected and docked in the enzyme pocket. Results: The docking result revealed that some of the compounds exhibited good potency against the virus and can be used further for developing new drug regimen. Conclusion: The compounds of natural origin could be a good target and can be used as lead compounds for the treatment of this dreadful disease.
Keywords: COVID19